Humanization of Medicine. Historical Development (Revista Iberoamericana de Bioética, 2018)
In negative terms we could say that the issue of health care humanization arises from the dehumanization of certain health practices; in positive terms we can instead go back to the most ancient roots of the humanitas that medicine has embodied. Nevertheless, even in this renewed interest, it has not always been possible to adequately humanize or re-humanize the actions of health workers. In history there have been different health care patterns (that this article briefly discusses) and various pressures, both religious (such as the great saints’ reformers of assistance) and secular, in order to humanize the health world. Today the need to renew this process is felt even more and the “humanization of health care” must be considered as a priority of current medicine.